Development and Characterization of Nanoparticles for the Delivery of Gemcitabine Hydrochloride - Rekha Khaira; Jyoti Sharma; Vinay Saini (The Scientific World Journal)
Gemcitabine (2,2-difluorodeoxycytidine) is a deoxycytidine analog, currently being used as a first-choice drug in pancreatic metastatic cancer. Gemcitabine is administered weekly as 30-minute infusion with starting dose ranging from 800 to 1250 mg/m2. The aim of the present work was to develop starch nanoparticles (NPs) for the delivery of gemcitabine hydrochloride that could reduce its dose related side effects and may prolong its retention time (24 hrs) for the treatment of pancreatic cancer. Nanoparticles were prepared by emulsification diffusion method with slight modifications. Size and morphology of nanoparticles were investigated. Particles were spherical in shape with slightly rough surfaces. Particle size and polydispersity index were 231.4 nm and 1.0, respectively while zeta potential of blank NPs and drug loaded NPs were found to be −11.8 mV and −9.55 mV, respectively. Percent entrapment efficiency of different formulations was around ∼54% to 65%. In vitro release profile studies showed that around 70%–83% of drug was released from different formulations. Anticancerous cell line studies were also performed in human pancreatic cell lines (MIA-PA-CA-2).